2016
DOI: 10.1016/j.vetmic.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Brachyspira hyodysenteriae isolated from apparently healthy pig herds following an evaluation of a prototype commercial serological ELISA

Abstract: Brachyspira hyodysenteriae, although "Brachyspira hampsonii" and Brachyspira suanatina 20 also cause SD. This study reports on the unexpected isolation of B. hyodysenteriae from pigs in 21 apparently healthy herds that gave positive reactions when tested with a prototype commercial 22 serological ELISA for detecting herds infected with B. hyodysenteriae (Priocheck ® Brachyspira 23 porcine Ab ELISA). The ELISA was tested with sera collected at abattoirs from 1,770 24 slaughtered pigs from 30 Australian herds, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 29 publications
(2 reference statements)
1
25
0
Order By: Relevance
“…These included breeding herds that underwent heightened surveillance as part of this study, including collection of colonic mucosa from healthy pigs at the abattoir. Results for six of these herds that were initially identified as infected through serological screening have been reported previously [15]. A similar situation was reported in an early Australian study, where an isolate of B .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These included breeding herds that underwent heightened surveillance as part of this study, including collection of colonic mucosa from healthy pigs at the abattoir. Results for six of these herds that were initially identified as infected through serological screening have been reported previously [15]. A similar situation was reported in an early Australian study, where an isolate of B .…”
Section: Discussionsupporting
confidence: 74%
“…Besides hemolysis, the block of six plasmid genes may encode other potential virulence factors that have been loosely associated with facilitating colonization [15,24,53]. Analysis of the distribution of this block of genes showed that most of the STs in the herds that were either thought to be free of SD or where the disease status was unclear did lack them, but this also commonly was the case for the isolates in STs in the herds with a history of SD (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that healthy pigs in some herds without disease may carry low numbers of virulent B. hyodysenteriae in their large intestines . The lack of a complete bacteriological ‘cure’ at the dose rates of kitasamycin used in this experiment is a potential drawback, since these treated animals potentially still will be infectious.…”
Section: Discussionmentioning
confidence: 99%
“…The etiological agent of SD is the anaerobic intestinal spirochaete Brachyspira hyodysenteriae [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%